PENGARUH PENERAPAN E-KINERJA DAN INTEGRITAS TERHADAP KINERJA PEGAWAI - Sisi Wahyuni (Journal of Education on Social Science (JESS), 2020)
This study aimed to identify the effect of the E-Kinerja (E-Performance) application and integrity on employee performance in OPD Payakumbuh City. This study used a quantitative research method. The research variable of this study consisted of independent variables, namely E-performance and integrity, while the dependent variable was employee performance. The population of this study were OPD employees in Payakumbuh, and the sample of this study was 97 respondents who were determined using the Slovin formula with a significant level of 10%. The data in this study were collected through questionnaires that were distributed to respondents using a Likert measurement scale. The analysis of this study used multiple linear regression test. The results showed that e-performance and integrity had significant influences on employee performance in OPD Payakumbuh City.